2017
DOI: 10.1186/s12939-017-0618-7
|View full text |Cite
|
Sign up to set email alerts
|

Individual and regional association between socioeconomic status and uncertainty stress, and life stress: a representative nationwide study of China

Abstract: BackgroundMany studies have examined the association between socioeconomic status (SES) and mental stress. Uncertainty stress is a prominent aspect of mental stress. Yet no research has ever empirically analyzed the impact of SES on uncertainty stress.MethodsStudents were identified through a multistage survey sampling process including 50 universities. Each student participant completed the Global Health Professions Student Survey (GHPSS) on Tobacco Control in China. Regional variables were retrieved from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 28 publications
6
48
2
Order By: Relevance
“…The higher the total score, the greater is the perceived level of stress. Consistent with prior practice, scores exceeding two on each item indicated "high stress" (Yang et al, 2007(Yang et al, , 2012(Yang et al, , 2017aWu et al, 2016). The Cronbach's α coefficient was 0.80 for uncertainty stress, 0.74 for life stress, and 0.61 for study stress in this study.…”
Section: Perceived Stresssupporting
confidence: 82%
See 3 more Smart Citations
“…The higher the total score, the greater is the perceived level of stress. Consistent with prior practice, scores exceeding two on each item indicated "high stress" (Yang et al, 2007(Yang et al, , 2012(Yang et al, , 2017aWu et al, 2016). The Cronbach's α coefficient was 0.80 for uncertainty stress, 0.74 for life stress, and 0.61 for study stress in this study.…”
Section: Perceived Stresssupporting
confidence: 82%
“…According to current studies, there are four forms of uncertainty stress: fate unpredictability, life goal uncertainty, social value uncertainty, and social change uncertainty (Wu et al, 2016;Yang et al, 2017a,b). One study underscored that socioeconomic inequalities were an antecedent of uncertainty stress (Yang et al, 2017a). In that study of college students, uncertainty stress was found to be related to one's social standing, access to material resources, and levels of social support (Yang et al, 2017a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These categories are consistent with the national standard for overweight and obesity utilized in China ( Department of Disease Control and Prevention, 2003 ). Self-report measures of overweight and obesity have been shown to be reliable in this population as there is a high correlation with objective measures for these variables (97.1% for the combined prevalence of overweight and obesity, and 98.8% for obesity ( Yang, Yang, Yu, Cottrell, & Jiang, 2017 ).…”
Section: Methodsmentioning
confidence: 99%